Dispersion pattern of Helopeltis antonii Signoret (Hemiptera: Miridae) on cashew plantation. - Siswanto,; Muhamad Awang, Rita; Omar, Dzolkhifli; Elna Karmawati, (2008)
Helopeltis antonii is one of the major pests in most cashew growing areas in Indonesia. The pest attacks cashew plants in the nursery and also in the fields which causes significant damage. Apart of cashew the insects have a lot of alternate host plants such as tea, cacao, neem, pepper, mangoes, and jamboes. This research was aimed at investigating the dispersion pattern of H. antonii in cashew plantation. The research was conducted in smallholder cashew plantation in Ngadirojo, Wonogiri, Central Java from March 2004 to May 2006. The observation of H. antonii population was carried out on 60 sample plants selected systematically in about 2 ha cashew plantation area every two weeks. Distribution analysis using various indices of dispersion and regression models was applied to evaluate the dispersion of H. antonii in cashew plantation. The result showed that variance to mean ratio (s2/x), Ç2, Lloyd mean crowding, Green’s coefficient of dispersion, and Taylor’s power law indicated aggregated distribution when the population was high during flushing-flowering seasons of cashew plants, and it indicated regular or random distribution when the population was low during postflowering seasons. The aggregated distribution on cashew plants indicated that there was a preferency to food sources of the plants and an individual behavior to aggregate. Therefore, sampling and monitoring H. antonii in cashew plantation should be carried out systematically during flushing-flowering seasons.